1990
DOI: 10.1152/jn.1990.63.6.1323
|View full text |Cite
|
Sign up to set email alerts
|

Tactile detection of slip: surface microgeometry and peripheral neural codes

Abstract: 1. The role of the microgeometry of planar surfaces in the detection of sliding of the surfaces on human and monkey fingerpads was investigated. By the use of a servo-controlled tactile stimulator to press and stroke glass plates on passive fingerpads of human subjects, the ability of humans to discriminate the direction of skin stretch caused by friction and to detect the sliding motion (slip) of the plates with or without micrometer-sized surface features was determined. To identify the associated peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(141 citation statements)
references
References 0 publications
0
134
1
1
Order By: Relevance
“…These afferents offer many types of information that may be of relevance for the control of fingertip forces in manipulation, for instance, information related to frictional slips and creep Srinivasan et al, 1990;Milner et al, 1991), the shape of the contact surface (Goodwin et al, 1995), and contact angle (Goodwin and Morley, 1987), as well as distribution within the contact area of normal and tangential forces Srinivasan et al, 1990;. Thus, information related to object shape in the present study should have been readily available from signals in populations of tactile afferents.…”
Section: Somatosensory Afferent Sourcesmentioning
confidence: 97%
“…These afferents offer many types of information that may be of relevance for the control of fingertip forces in manipulation, for instance, information related to frictional slips and creep Srinivasan et al, 1990;Milner et al, 1991), the shape of the contact surface (Goodwin et al, 1995), and contact angle (Goodwin and Morley, 1987), as well as distribution within the contact area of normal and tangential forces Srinivasan et al, 1990;. Thus, information related to object shape in the present study should have been readily available from signals in populations of tactile afferents.…”
Section: Somatosensory Afferent Sourcesmentioning
confidence: 97%
“…LaMotte and Srinivasan (1991; see also Srinivasan, Whitehouse, & LaMotte, 1990) have found that an array of dots or bars that are on the order of 0.1,um in height can be detected by scanning, but not by static, touch. Subjects reported that their detection ofthese ultrafine stimuli (to which only Pacinian afferents were found to respond) was based on vibratory sensations.…”
mentioning
confidence: 99%
“…In order for the identification and control procedures to be robust, continuous monitoring of contact conditions with tactile sensors is absolutely necessary. In humans, specialized tactile mechanoreceptors enable detection of slipping of objects on the skin [9,12] and analogous robotic sensors have also been developed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Suppose fc falls below the lower bound, detection of slip is of paramount importance, and can be accomplished by specialized tactile slip detectors. In fact, it has been demonstrated that primates use tactile sensors to detect slip [9]. In human studies, it has been shown that subjects apply an external force which is about 30% more than the lower bound needed to overcome slip [12].…”
Section: Meeting Constraintsmentioning
confidence: 99%
See 1 more Smart Citation